Immunohistochemical expression of OCT4 and CD44 in major and minor salivary gland neoplasms - Jamile Marinho Bezerra de Oliveira Moura; Amanda Katarinny Goes Gonzaga; Salomão Israel Monteiro Lourenço Queiroz; Manoela Domingues Martins; Leão Pereira Pinto; Lélia Batista de Souza (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract The aim of this study was to identify tumor parenchyma cells exhibiting immunohistochemical profile of stem cells by evaluating the immunoreactivity of OCT4 and CD44 in a number of cases of salivary gland neoplasms. The sample consisted of 20 pleomorphic adenomas, 20 mucoepidermoid carcinomas, and 20 adenoid cystic carcinomas located in major and minor salivary glands. The expression of OCT4 and CD44 was evaluated by the percentage of positive cells and the intensity of expression. All studied cases showed positive expression of OCT4 and CD44 and higher values than the control groups. For OCT4, luminal and non-luminal cells were immunostained in the case of pleomorphic adenomas and adenoid cystic carcinomas. Moreover, the immunoreactivity of CD44 was particularly evident in the non-luminal cells of these lesions. In mucoepidermoid carcinomas, there was immunoreactivity for both markers in squamous and intermediate cells and absence of staining in mucous cells. For both markers, a significantly higher immunostaining was verified in neoplasms located in the major salivary glands compared with lesions in minor salivary glands (p<0.001). In the total sample and in minor salivary glands, malignant neoplasms exhibited higher immunoreactivity for OCT4 than pleomorphic adenoma. A significant moderate positive correlation (r = 0.444 and p ≤ 0.001) was found between OCT4 and CD44 immunoexpression in the total sample. The high expression of OCT4 and CD44 may indicate that these proteins play an important role in identifying tumor stem cells.